Creation and confirmation of heterozygous clones in Japanese flop, Paralichthys olivaceus by microsatellite marker - Zhang Yen; Zee Chan; V. E. Zedong (Advances in Aquaculture and Fisheries Management, 2019)
Mitotic gynogenetic diploids Japanese flounder Paralichthys olivaceus were produced by activating eggs with ultra violet (UV) irradiated sperm of red sea bream (Pagrus major), followed by hydrostatic pressure treatment to block the first mitotic division. By crossing two mitotic gynogenetic diploid females with two males, two heterozygous clones of Japanese flounder were produced. Microsatellite marker was used to confirm the genetic status of maternal parents and their progenies. 20 polymorphic microsatellite markers were chosen, covering 16 out of the total 24 linkage groups. The four maternal parents used in this experiment were completely heterozygous, while four mitotic gynogenetic diploids were homozygous for each marker. The genotypes of heterozygous clone progenies were identical and the combination of parental alleles, demonstrates the successful development of cloning.